Penyuluhan Kesehatan Peningkatan Kesadaran Cuci Tangan Pakai Sabun (CTPS) Melalui Program UKS Di Sekolah Dasar Mis Pasi Jambu - Tasnimin (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Handwashing with Soap (CTPS) is one of the key indicators of Clean and Healthy Living Behavior (PHBS) proven effective in preventing infectious diseases, especially among school-aged children. However, the practice of CTPS in Aceh Province remains low, only 30.8%, thus requiring educational interventions in elementary schools. This community service aimed to improve the knowledge, attitudes, and skills of students at MIS Pasi Jambu, Aceh Barat District, in practicing CTPS through strengthening the role of the School Health Program (UKS). The method used was a participatory approach with strategies including interactive lectures, discussions, demonstrations, and direct practice. The results showed a significant increase in students’ knowledge and skills in performing CTPS according to WHO standards. In addition, behavioral changes emerged, with students developing the habit of washing hands before meals and after activities, while UKS teachers were strengthened as facilitators of healthy behavior in schools. This activity successfully fostered collective awareness and the initial stage of social transformation towards a clean and healthy lifestyle in the school environment.